A Method to Launch Sustainability Reporting in SMEs: The B Corp Impact Assessment Framework - Shields, Jeffrey F.; Shelleman, Joyce M. (Journal of Strategic Innovation and Sustainability, 2017)
As sustainability reporting and management rapidly increase in importance, SME managers must learn how to integrate sustainability issues and reporting into their businesses. This paper offers an overview of an accessible organized approach that SME management can use to begin. The B Lab’s “B Impact Assessment” offers a method that could suit resource constraints typical of many SMEs with its presentation of key sustainability issues in a format oriented toward smaller companies